Proceso de la devolución del impuesto al valor agregado (IVA) y su impacto en los resultados económicos de la empresa ESL - ROSES C.A, ubicado en el cantón Latacunga, provincia de Cotopaxi, en los periodos 2015-2017 - Yupangui Llugcha, Jesseña Maribel (2019)
Lack of liquidity is one of the factors that prevent flower exporting companies from achieving higher levels of competitiveness, which is caused by various factors, one of them is the payment of indirect taxes as is the case of VAT, that is generated in their purchases and that cannot be compensated in their sales, because the exports go to the world market with 0% tariff. In this way, it has been considered relevant through this research evaluate the impact generated by the process of the return of VAT and its impact on the economic results of the company ESL - ROSES C.A, located in Latacunga Canton, Cotopaxi Province, in the periods 2015-2017. From a brief review of both the conceptual basis and current legal regulations governing the right to VAT refund and the description of the VAT refund procedure for exporters of goods. The methodology used for the elaboration of this research is based on the bibliographical review, on the systematic and reflexive analysis of secondary sources, related to the field research that consists of the collection of data without manipulating or controlling whichever variable, using the technique of the observation and the interview applied to the Chief and accounting assistant, which was indispensable to know and analyze the different causes generated by the process of the return of VAT in the economic results in the company ESL - ROSES C.A. Subsequently, with the information provided by the company ESL ROSES CA, the respective financial analysis is carried out by means of liquidity indicators, it is also pertinent to determine the values calculated by the company versus the value returned by the Tax Administration, in order to determine the impact generated by the VAT refund on the economic results of the exporting company.